HIV and hepatitis C Virus in internally displaced people with and without injection drug use experience in the region of Shida Kartli, Georgia - Adrian Trovato; Maka Gogia; Ana Aslanikashvili; Tamuna Kasrashvili; Ganna Kovalenko; Anna Yakovleva; Britt Skaathun; Tetyana I. Vasylyeva (BMC Research Notes)
Abstract Objective Internally displaced persons (IDPs) can have limited access to HIV and hepatitis C Virus (HCV) treatment and prevention. IDPs comprise > 7% of Georgian population but prevalence and levels of HIV and HCV knowledge in this population remain unknown. We tested 100 IDPs in Georgia for HIV and HCV, many of whom had drug injecting experience, and interviewed them about their migration experience, sexual and drug injecting practices, and HIV/HCV transmission knowledge. Results The average age of participants was 37.5 years (range 18–63); 31% were women. Almost half (N = 48) of participants reported ever injecting drugs; 17% of those (N = 8) started injecting drugs within the last year. Anti-HCV and HIV prevalence was 11% and 0%, respectively. Fewer people without drug use experience compared to people who inject drugs correctly answered all questions on the HIV knowledge test (13% vs. 35%, p = 0.015) or knew where to get tested for HIV (67% vs 98%, p < 0.001). There was no difference in HCV knowledge between the two groups. HIV and HCV prevalence remains low among Georgian IDPs, but levels of HIV knowledge were much lower than levels of HCV knowledge.